Produtividade da alface cv. Isabela cultivada sob diferentes níveis de composto orgânico e de biofertilizante - Santos, Antonio Gomes dos (2011)
Lettuce is one of the most commonly consumed by Brazilian hardwoods, and has therefore been sought production alternatives that reduce their impact on ecosystems. The objective of this study was to evaluate the productivity and occurrence of pathogens in lettuce cv. Isabela grown under different levels of organic compounds and biofertilizers. The work was conducted at the Experimental Farm Green living, located in the Itabaiana-SE in Acrisol. The experiment was conducted under fiel conditions in randomized complete block randomized in a factorial 4 x 6, ie, four levels of organic compound compost (0, 3, 6 and 9 kg/m2) and six levels of biofertilizer (0, 2, 4, 6, 8 and 10 L/m2), with three replications. Significant effects at doses of organic compost and biofertilizer on variables for interaction among gead dameter, fresh weight of edible leaves, fresh weight. The organic manure incorporated into the soil increases the diameter of the head of lettuce, fresh mass, stem fresh weight, fresh weight of edible leaves, necrotic leaf fresh weight, fresh shoot and total fresh weight. Treatments 6 and 9 kg/m2 of organic compound are better treatments for the development of the lettuce and the biofertilizer reduces the incidence of galls on the roots of cv. Isabela.